Redescription of Pararhaphe and review of Arhaphe (Hemiptera: Heteroptera: Largidae) of America north of Mexico - Stehlík, Jaroslav L.; Kment, Petr (Zootaxa, 2011)
The genus Pararhaphe Henry, 1988 (= Japetus Distant, 1883) (Largidae: Arhaphinae) is redescribed based on the type species Pararhaphe sphaeroides (Distant, 1883), considered monotypic, and its generic status is confirmed. The genus Jarhaphetus Bliven, 1956, syn. restit., is confirmed as junior synonym of Arhaphe Herrich-Schaeffer, 1850. Four species of the genus Arhaphe occurring in the United States are recognised and keyed: Arhaphe arguta (Bliven, 1956) comb. res- tit. (= Jarhaphetus argutus Bliven, 1956; = Arhaphe snowi Bliven, 1973, syn. nov.); Arhaphe breviata Barber, 1924; Arhaphe carolina Herrich-Schaeffer, 1850; and Arhaphe mimetica Barber, 1911, comb. restit. (from Pararhaphe mimetica (Barber, 1911)). Arhaphe cicindeloides Walker, 1873 (= Arhaphe divisa Brailovsky, 1981, syn. nov.) is redescribed based on type specimens; all the previous records of A. cicindeloides from the United States are regarded as misidentifications of A. arguta. Lectotypes of A. cicindeloides and A. mimetica are designated. The literature, bionomics, and distribution of all the mentioned taxa is reviewed.